ANALISIS KETERAMPILAN MENGAJAR GURU PAUD DI KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI - Rindi Antika; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is aimed to know the teaching skill of paud teacher in sub district of Kuantan, Kuantan Singingi district. The research used descriptive method. The sample used in this study were 50 teachers. The data collection technique used is the dispersion of questionnaires. Data analysis technique using percentage calculation with formula F / N x 100%. By using SPSS 17 program. Based on data analysis seen in whole aspect of teacher's teaching skill at Kindergarten in Hulu Kuantan Subdistrict, it is obtained 637 score with 51% percentage is in medium category or enough. It means that the teaching skills of PAUD teachers in Kecamatan Hulu Kuantan are quite capable of performing their duties as teachers of Early Childhood Education (PAUD).Keywords: Teaching Skills, Teachers